Retinal pigment epithelial atrophy following indocyanine green dye-assisted surgery for serous macular detachment - Hussain Nazimul; Jalali Subhadra; Rani Alka; Rawal Hema (Indian Journal of Ophthalmology, 2008)
To report subretinal migration of indocyanine green dye (ICG) and subsequent retinal pigment epithelial (RPE) atrophy during macular surgery for serous macular detachment. A 65-year-old woman presented with residual epiretinal membrane and serous detachment of the macula following vitreoretinal surgery for epiretinal membrane. She underwent resurgery with ICG-assisted internal limiting membrane peeling and intraocular tamponade. Intraoperatively a large area of subretinal ICG was seen with subsequent RPE mottling and atrophy of the macula in the area involved during follow-up. This case demonstrates that subretinal migration of ICG is possible and can be toxic to RPE.